GRICE’S CONVERSATIONAL MAXIMS AND ISLAMIC CONVERSATIONAL RULES - Ruminda Ika Yatmikasari (Universitas Islam Negeri Mataram, Indonesia, 2018)
In their daily activities, people will need to interact with other people. In this interaction, people use language as a means of communication. A conversation, as a way of people doing communication, can only take place by the presence of both speakers and hearers under a particular circumstance. As one of the pragmatic aspects, cooperative principle becomes something that should be noticed in a conversation. Grice (1975) said that the conversation will run well if both of the speaker and hearer obey the rules of conversation which he arranged into four conversational maxims, namely Maxim of Quantity, Maxim of Quality, Maxim of Relevance, and Maxim of Manner. For Islamic followers, these conversational rules, however, have long time been known well since Islam has ruled its people to treat other people well in all aspects, not to mention in speaking. This present article will see how Grice’s conversational maxims, which were proposed in 1975, are in line with the Islamic conversational rules which were mentioned in Quran and hadith long time ago, since 600s. It means that this broadly-known pragmatic theory is not something new in Islam. It is also to prove that Islam, to some extent, is the source of knowledge and value which are often developed further by western scholars. Keywords: pragmatics, Grice’s conversational maxims, Islamic conversational rules